Nitrogen Fertilization Effects on Biomass Production and Yield Components of Miscanthus ×giganteus - Lee, Moon-Sub; Wycislo, Andrew; Guo, Jia; Lee, D. K.; Voigt, Thomas (Frontiers in Plant Science, 2017)
GraGrasses such as Miscanthus × giganteus and Panicum virgatum (switchgrass) can potentially be used to produce bioenergy on a large scale in the Midwestern USA. The biomass productivity of these warm-season perennial grasses, particularly M. × giganteus, can be substantial, even when grown with limited inputs. The literature, however, varies regarding the nitrogen requirements for M. × giganteus biomass production. In addition, there is a lack of information that identifies the yield-component(s) (including total tiller number, tiller weight, total tiller diameter, total tiller height, phytomer number, reproductive tiller number, vegetative tiller number, reproductive tiller height, vegetative tiller height, reproductive tiller diameter, vegetative tiller diameter, and reproductive tiller phytomer number) that contributes to M. × giganteus biomass yields. Thus, the objective of this study was to examine the effects of fertilization on biomass yield and individual M. × giganteus plant-yield components. Plots of M. × giganteus were planted in 2008 in Urbana, IL, USA, and received annual applications of 0, 60, or 120 kg N ha-1. Miscanthus × giganteus productivity increased when nitrogen was applied; between 2011 and 2014, nitrogen applications of 60 or 120 kg N ha-1 produced average annual yields of 22.0 dry Mg ha-1 compared to 11.8 dry Mg ha-1 for unfertilized M. × giganteus. Both the total number of tillers per m2 and the tiller weight also increased as N-application rates increased. Our results indicate that increased reproductive tiller density and tiller weight with increased N fertilization increased M. × giganteus biomass yield.